O direito à educação e o Programa Novo Mais Educação, no município de Bayeux - Santos, Stefany Thyene Albuquerque dos (2020)
This work addressed the Mais Educação Program (PME) as a policy of social inclusion and its contributions to education in the municipality of Bayeux. The general objective of the research was to analyze the development of the Novo Mais Educação Program (PNME) and its contributions to education, and, as specific objectives, to identify the objectives of the program, to analyze the proposal presented and the practices developed in the school that we call X, and highlight the importance of the program for education. The children who were part of the program are mostly children who were and continue to be in conditions of social vulnerability and extreme poverty. We were able to see, with the research, the importance of the program for education, mainly due to the changes that happened in the school. Respondents reported that there was improvement in learning, improvement in motivation, more willingness to learn and improvement in cognitive development. It was also found that in the municipality of Bayeux in 2017, the period studied, there were a total of 27 schools served by the PME. We emphasize that the resources of the programs were approved in the previous year's budget, that is, in 2016, under the government of President Dilma Rousseff. In 2017, after the president's departure, Michel Temer assumed the presidency and approved the 2018 budget, when he reduced the program to just 12 schools with the number of 1,642 students. The amount received from the first installment (execution in five months) of the PNME 2018 resource was R $ 322,710.00. In 2019, the program was further reduced, with a maximum of 7 to 8 schools expected. Thus, we verify that, with the changes of government from PT (Partido dos Trabalhadores) to PMDB (Partido do Movimento Democrático Brasileiro), and from the latter to PSL (Partido Social Liberal), the resources destined to finance the PNME are gradually decreasing. . And where are the children? Are they going back to the streets? Are they in child labor? In our experience, during a significant period, it was possible to notice an improvement in language learning, in the quality of life of the children and the damage caused by the discontinuity of the program was found